Improving higher education in Malawi for competitiveness in the global economy - Mambo, Michael M. (World Bank e-Library., 2016)
As the Government of Malawi investigates options to expand access to higher education and improve the quality of higher education provision, the objective of this report is to contribute to an improved understanding of the challenges confronted by the higher education sub-sector in Malawi. The report summarizes the key findings of an in-depth study of factors affecting access and equity in the Malawian higher education sub-sector, the quality and relevance of educational outputs, the financing of the sector, and the frameworks structuring governance of the sector and its management. The study was initiated in response to a request from the Government of Malawi, to the World Bank, to support the Ministry of Education, Science and Technology (MoEST) in its pursuit of financially sustainable policy options to increase equitable access to higher education, and to improve the quality of higher education provision in alignment with the needs of the labor market.